1985
DOI: 10.1037/h0080145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of auditory deprivation on successive processing.

Abstract: This article reviews psychological studies of sequential memory in hearing impaired subjects. Such studies are important for two main reasons. Firstly, deaf students and adults can be viewed as natural experiments. As such, they afford a possible means whereby more might be learned about "normal processors" of information (Conrad, 1979). Secondly, the effects of prelingual auditory deprivation are potentially devastating and have defied psychological and educational interventions (Quigley & Kretschmer, 1982). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, deaf and hearing individuals have been found to perform equally well when tested on free recall tasks that typically exceed the capacity of the phonological buffer and its rehearsal process (D. Bavelier, Newport, et al, 2008; Cumming & Rodda, 1985; Hanson, 1982, 1990; Krakow & Hanson, 1985). Thus, both the ‘Auditory Scaffolding Hypothesis’ and this latter view predict lesser performance in deaf than hearing individuals on tasks that require serial order recall of verbal material.…”
Section: Temporal Order Deficits Following Auditory Deprivationmentioning
confidence: 99%
“…Similarly, deaf and hearing individuals have been found to perform equally well when tested on free recall tasks that typically exceed the capacity of the phonological buffer and its rehearsal process (D. Bavelier, Newport, et al, 2008; Cumming & Rodda, 1985; Hanson, 1982, 1990; Krakow & Hanson, 1985). Thus, both the ‘Auditory Scaffolding Hypothesis’ and this latter view predict lesser performance in deaf than hearing individuals on tasks that require serial order recall of verbal material.…”
Section: Temporal Order Deficits Following Auditory Deprivationmentioning
confidence: 99%
“…Other works shows that deaf subjects, unlike hearing subjects, show no preference for forward over backward recall (Andin, Rudner & Rönnberg, 2008; O’Connor & Hermelin, 1976; Wilson et al ., 1997). In a review of the literature on the effects of auditory deprivation on successive processing, Cumming and Rodda (1985) came to the conclusion that the spatial bias of deaf individuals resulting from sign language use seems to result in a decreased emphasis on temporal ordering. Thus, it is well established that deafness leads to differences in temporal processes and as temporal coding plays a key role in working memory processing, these differences may to a certain degree account for intermodality span differences.…”
Section: Deafness Sign Language and Higher Cognitive Functionsmentioning
confidence: 99%
“…Are students with hearing loss poor in higher cognitive skills such as reasoning and problem solving? It has been suggested that as cognitive functions move from representational processes to higher symbolic modes, the likelihood of individuals with hearing loss completing such tasks diminishes (Cumming & Rodda, 1985). Other studies generally confirm this impression (Arnold & Walter, 1979;Furth, 1964;Quigley & Kretschmer, 1982).…”
mentioning
confidence: 78%